Olig2+ single-colony-derived cranial bone-marrow mesenchymal stem cells achieve improved regeneration in a cuprizone-induced demyelination mouse model - Deqing Peng; Ruijie Lu; Leyao Lü; Qing Yao; Kaichuang Yang; Yunfeng Xu; Xiaoming Feng; Ruolang Pan; Yuyuan Ma (Journal of Zhejiang University-SCIENCE B, 2024)

Recent progress in mesenchymal stem cell-based therapy for acute lung injury - Jinfeng Liang; Weiyou Dai; Shihang Xue; Feifei Wu; Enhai Cui; Ruolang Pan (Cell and Tissue Banking, 2024)

Luteolin suppresses oral carcinoma 3 (OC3) cell growth and migration via modulating polo-like kinase 1 (PLK1) expression and cellular energy metabolism - Pengfei Gao; Wentao Zhang; Yujie Lin; Ruijie Lu; Zijian Lou; Gang Lu; Ruolang Pan; Yunfang Chen (Journal of Zhejiang University-SCIENCE B, 2023)

Estrogen upregulates DNA2 expression through the PI3K-AKT pathway in endometrial carcinoma - Xinyan Wang; Xiuling Xu; Ting Zhang; Yang Jin; Sheng Xu; Lifeng Chen; Yucheng Lai; Ling Zhang; Ruolang Pan; Yan Yu (Journal of Zhejiang University-SCIENCE B, 2023)

DEHP mediates drug resistance by metabolic reprogramming in colorectal cancer cells - Yue Wu; Ruijie Lu; Yujie Lin; Jinjin Wang; Zijian Lou; Xiaochun Zheng; Ling Zhang; Ruolang Pan; Gang Lu; Qingxia Fang (Environmental Science and Pollution Research, 2023)
Long-term exposure to diethylhexyl phthalate (DEHP), an endocrine-disrupting chemical (EDCs) and plasticizer widely used in consumer products, has been reported to be significantly positively correlated with increased risks of different human diseases, including various cancers, while the potential effect of DEHP on colorectal cancer progression was little studied. In the present study, we showed that DEHP could trigger the metabolic reprogramming of colorectal cancer cells, promote cell growth and decrease fluorouracil (5-FU) sensitivity. Mechanistic studies indicated that DEHP could reduce glycolysis activity and increase oxidative phosphorylation (OXPHOS) in SW620 cells. In addition, in vivo experiments showed that DEHP promoted tumorigenic progression and decreased survival time in mice. Collectively, our findings suggest that DEHP may be a potent risk factor for colorectal cancer development.

Targeting TRMT5 suppresses hepatocellular carcinoma progression via inhibiting the HIF-1α pathways - Qiong Zhao; Luwen Zhang; Qiufen He; Hui Chang; Zhiqiang Wang; Hongcui Cao; Ying Zhou; Ruolang Pan; Ye Chen (Journal of Zhejiang University-SCIENCE B, 2023)

Establishment and characterization of IPS-OGC-C1: a novel induced pluripotent stem cell line from healthy human ovarian granulosa cells - Zhiqiang Wang; Xiaojia Hu; Qiufen He; Jingbo Lai; Ruolang Pan; Jing Zheng; Ye Chen (Human Cell, 2022)

Current status and future prospects of patient-derived induced pluripotent stem cells - Zhiqiang Wang; Jing Zheng; Ruolang Pan; Ye Chen (Human Cell, 2021)